2015
DOI: 10.1002/ese3.67
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous and homogenous catalysts for hydrogen generation by hydrolysis of aqueous sodium borohydride (NaBH4) solutions

Abstract: It is clear that in order to satisfy global energy demands whilst maintaining sustainable levels of atmospheric greenhouse gases, alternative energy sources are required. Due to its high chemical energy density and the benign by-product of its combustion reactions, hydrogen is one of the most promising of these. However, methods of hydrogen storage such as gas compression or liquefaction are not suitable for portable or automotive applications due to their low hydrogen storage densities. Accordingly, much rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 231 publications
(105 citation statements)
references
References 169 publications
0
96
0
Order By: Relevance
“…The hydrogen capacity can be controlled by varying the alloy combination and compound ratio. However, some of the alloy compounds encounter kinetic difficulties, and their hydrogen storage capacity is relatively low in the range of 1.4 wt% to 3.6 wt% H 2 for portable applications [90,117]. Asano et al [118] reported that the hydrogen sorption kinetics and the thermal stability of metal hydrides are related to the crystal lattice structure of the alloy because the interstitial sites of the crystal lattice can be occupied by hydrogen atoms.…”
Section: Alloyingmentioning
confidence: 98%
“…The hydrogen capacity can be controlled by varying the alloy combination and compound ratio. However, some of the alloy compounds encounter kinetic difficulties, and their hydrogen storage capacity is relatively low in the range of 1.4 wt% to 3.6 wt% H 2 for portable applications [90,117]. Asano et al [118] reported that the hydrogen sorption kinetics and the thermal stability of metal hydrides are related to the crystal lattice structure of the alloy because the interstitial sites of the crystal lattice can be occupied by hydrogen atoms.…”
Section: Alloyingmentioning
confidence: 98%
“…(1)] is spontaneous and exothermic (240±5 kJ mol −1 ); however, the kinetics is severely deteriorated when the pH value is increased because of the formation of basic byproducts (B(OH) 3 /B(OH) 4 − at p K a =9.24) . Total hydrolysis requires then the use of an accelerator, either an acid or more broadly a metal‐based catalyst . Hence, NaBH 4 , the x +4 mol of H 2 O [Eq.…”
Section: Sodium Borohydridementioning
confidence: 99%
“…[46] Total hydrolysis requires then the use of an accelerator,e ither an acid or more broadly am etal-based catalyst. [47][48][49][50] Hence, NaBH 4 ,t he x + 4mol of H 2 O[ Eq. (3)],t he accelerator, the borate byproducts,a nd the product H 2 have to be separately considered to gain ac omprehensive understandingo ft he reaction:…”
Section: Preliminary Commentsmentioning
confidence: 99%
“…16 Hydrolysis of NaBH 4 and concomitant H 2 release can be controlled with the help of a catalyst. 17 The reaction temperature is mostly set between 10 and 40…”
Section: Liquid-state Hydrogen Storagementioning
confidence: 99%